Equivalent wire model and travelling wave mode method to analyse the radiated emission of a bent microstrip line - Yee, See Khee (2009)
Nowadays, expeditious developments in the electrical and electronic territory due to endless demands from the markets have driven the operation frequency of the system into the gigahertz region. This had evolved into a more effectual-performance system, but also inflicts a lot of difficulties to the designers, for examples Electromagnetic Interference (EMI) problem and Signal Integrity (SI) issue. The integrity of circuit layout is inevitably compromised by bifurcated traces for examples T -junctions, Y -junctions, right-angle bends or left-angle-bends and steps planar transmission lines in order to fulfil the needs of a denser printed circuit boards. However, bifurcation often induces impedance mismatching resulting in reflection, radiated emission and power loss. This research is to investigate the radiated emission of 0°,45° and 90° bent microstrip lines by using an analytical fODnulation followed by computer simulation and experimental measurements for validation purposes. The novelty of this research is the implementation of travelling wave mode (TWM) method on bent microstrip line by adopting the equivalent wire model. The reliability of the formulation is proven from the agreement between the analytical results and computer simulation, especially in predicting the E¢ component. The analytical results clearly showed the significance of the bent in altering the radiation pattern of the microstrip line. Increasing the operating frequency and microstrip's width tend to produce more emission. One of the electric field components, Eo is almost symmetrical with respect to the bent angle/2 line on the plane of the microstrip line, while the E¢ component radiates strongly into the bent angle + bent anglel2 direction. The magnetic field on the bent microstrip line experiences an abrupt change at the location of the bent. This change becomes apparent as the bent angle increases. Future work should focus on improving the analytical fornmlation so that it can predict the Eo component with higher accuracy. FurtheDnore, effort can also be made on generating algorithm which takes into consideration the composite electric field radiation of all the bents on a practical printed circuit board.